Mesenchymal Stem Cells and Islet Cotransplantation in Diabetic Rats: Improved Islet Graft Revascularization and Function by Human Adipose Tissue-Derived Stem Cells Preconditioned with Natural Molecules - Giuseppe Cavallari (Cell Transplantation, 2012)
Hypoxia plays an important role in limiting the engraftment, survival, and function of intrahepatically transplanted islets. Mesenchymal stem cells (MSCs) were recently used in animal models of islet transplantation not only to reduce allograft rejection but also to promote revascularization. Among different possible origins, adipose tissue represents a novel and good source of MSCs. Moreover, the capability of adipose tissue-derived stem cells (ASCs) to improve islet graft revascularization was recently reported after hybrid transplantation in mice. Within this context, we have previously shown that hyaluronan esters of butyric and retinoic acids can significantly enhance the rescuing potential of human MSCs (hMSCs). Here we evaluated whether ex vivo preconditioning of human ASCs (hASCs) with a mixture of hyaluronic (HA), butyric (BU), and retinoic (RA) acids may result in optimization of graft revascularization after islet/stem cell intrahepatic cotransplantation in syngeneic diabetic rats. We demonstrated that hASCs exposed to the mixture of molecules are able to increase the secretion of vascular endothelial growth factor (VEGF) as well as the transcription of angiogenic genes, including VEGF, KDR (kinase insert domain receptor), and hepatocyte growth factor (HGF). Rats transplanted with islets cocultured with preconditioned hASCs exhibited a better glycemic control than rats transplanted with an equal volume of islets and control hASCs. Cotransplantation with preconditioned hASCs was also associated with enhanced islet revascularization in vivo, as highlighted by graft morphological analysis. The observed increase in islet graft revascularization and function suggests that our method of stem cell preconditioning may represent a novel strategy to remarkably improve the efficacy of islets-hMSCs cotransplantation.